IMPLEMENTATION OF REGULATIONS BRING FOODS TO SCHOOL TO CONSUMPTIVE BEHAVIOR OF ELEMENTARY SCHOOL STUDENTS IN PURWAKARTA - Deri Fadly Pratama; Deden Herdiana Altaftazani; Anugrah Ramadhan Firdaus (PrimaryEdu : Journal of Primary Education, 2019)
This research is motivated by the issuance of government policies relating to the progress of the world of education. The purpose of this study is to examine the implementation of the policy on consumptive behavior among elementary school students. The research method used is a case study. Subjects in the study were 100 students who were divided into 3 (three) classes at the high class level at SDN Ciseureuh Kahuripan Pajajaran Purwakarta district, as well as providing relevant counseling to teachers, parents, community leaders and related stakeholders. The instrument used to measure the level of implementation in this regulatory policy is the observation and interview sheets while for the assessment of consumptive behavior is a matter of multiple choice, observation sheets and questionnaires given. The treatment given to stakeholders is counseling that optimizes the implementation of regulations to bring provisions to schools in the form of rules and policy levels using a persuasive approach. The results showed that the implementation of regulations bringing provision to schools initiated by Purwakarta district government significantly decreased the consumptive nature compared to students who did not receive treatment from the government regulations. Thus it can be concluded that the implementation of the regulation of bringing provisions to schools initiated by the Purwakarta district government can suppress the consumptive nature of elementary school students.